Unconventional Politics : Nineteenth-Century Women Writers and U.S. Indian Policy - Dean, Janet, 1965- (Book collections on Project MUSE., 2016)
"Throughout the nineteenth century, Native and non-Native women writers protested U.S. government actions that threatened indigenous people's existence. The conventional genres they sometimes adopted--the sensationalistic captivity narrative, sentimental Indian lament poetry, didactic assimilation fiction, and the mass-circulated commercial magazine--typically had been used to reinforce the oppressive policies of removal, war, and allotment. But in Unconventional Politics Janet Dean explores how four authors, Sarah Wakefield, Lydia Huntley Sigourney, the Muscogee/Creek S. Alice Callahan, and the Cherokee Ora V. Eddleman, converted these frameworks to serve a politics of dissent. Intervening in current debates in feminist and Native American literary criticism, Dean shows how these women advocated for Native Americans by both politicizing conventional literature and employing literary skill to respond to national policy. Dean argues that in protesting U.S. Indian policy through popular genres, Wakefield, Sigourney, Callahan, and Eddleman also critiqued cultural protocols and stretched the contours of accepted modes of feminine discourse. Their acts of improvisation and reinvention tell a new story about the development of American women's writing and political expression"--